The local knowledge of the rural people on species, role and hunting of birds: Case study in Karangwangi Village, West Java, Indonesia - JOHAN ISKANDAR; BUDIAWATI SUPANGKAT ISKANDAR; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2016)
Iskandar J, Iskandar BS, Partasasmita R. 2016.The Local knowledge of the rural people on species, role, and hunting of birds: case study in Karangwangi village, Cidaun, West Java, Indonesia. Biodiversitas 17: 435-446. Based on the ecological history, in the past many villages of in Indonesia including in West Java had a high diversity of birds. Nowadays, however, the diversity of birds in some villages of West Java has tended to decrease due to many factors, namely habitat loss, the use of pesticides, and intensive illegal bird hunting. The objective of this paper is to elucidate the local knowledge of Karangwangi village, West Java on species, role, and hunting of birds. Method used in this study is the qualitative and ethnoornithological approach with descriptive analysis. Results of study show that the Karangwangi people have a very good knowledge on bird species, particularly on level species/specific. Various bird species are traditionally classified into nine local categories (folk classification), namely based on distinctive voice/vocalization, morphological characteristic, special color, distinctive behavior, time activity, special common habitat, migrant, nest characteristics, and role in the ecosystem. Based on the rural people perception, the role of birds can be divided into two categories, namely notorious and beneficial birds. The diversity of rural birds has tended decrease over time due to various factors, including illegal bird hunting for various purposes of the village people, such as keep a bird in cages and bird trading. The study suggests the perception of rural people on birds have changed caused of socio-economic and cultural changes. Nowadays the bird hunting in the rural area has tended to shift from a purely subsistence form towards a more commercial form and, thus, to conserve bird species the study on ethnoornithology considered as a very important, and socio-economic and cultural rural people aspects might be integrated to national as well as international bird conservation programs.